Fidelity of Fetal Foot Length in Association with Femur Length to Determine Ultrasonographic Fetal Gestational Age in Uncomplicated Pregnant Women of Chattogram, Bangladesh (IAHS Medical Journal, 2025)
Background: Ultrasonography is the most admissible method for gestational age estimation worldwide. The current study was aimed to determine the accuracy of fetal foot length and its correlation with femur length for fetal gestational age prediction in among Bangladeshi uncomplicated pregnant women of Chattogram district.Materials and methods: This cross-sectional observational study, conducted in Chittagong Medical College, Chattogram, included 200 uncomplicated pregnant women of 15th to 28th weeks of gestation. Fetal biometric parameters such as fetal foot length and femur length were measured by 2D ultrasonography. For statistical analysis Pearson’s correlation test and correlation-regression analysis was done and p-value was considered significant if it was